Diseño de un modelo de gestión de portafolios para empresas del sector de servicios de aseo, gas e infraestructura de un grupo empresarial (2015)
The work of degree was developed in the Business Group of Llano, formed by the companies Bioagrícola del Llano S.A. ESP, Inversiones Alis Ltda. And Llanogas S.A. ESP. Grupo Empresarial del Llano needed a process to easily define which projects to implement in order to leverage the objectives defined by the organization, according to prioritization criteria, which will facilitate decision-making on them and constant monitoring. Therefore it was considered important to improve the management of the projects and initiatives of the organization, define a portfolio that allows to consolidate, group and manage them in a centralized manner, so that it is possible to ensure the correct management of them, and the scope of their objectives, adding value to the organization. Due to the above, this work of degree raised four objectives: First, to make a diagnosis of the current situation of the organizations belonging to the Business Group of the Llano that allows establishing the baseline for the design of the model; second, to design a methodological proposal for the management of the portfolio of projects of the Empresarial del Llano Group based on the Project Portfolio Standard of the PMI (3rd edition) and according to the procedures and practices of the organizations analyzed; third, define a guide for the implementation of the proposed methodology, including the deliverables and their respective responsible within each of the organizations that make up the group; and fourth, after implementing a pilot test for the validation of the proposed methodology, by the project sponsor and establishing measurement and monitoring mechanisms for the portfolio management model to be implemented in the business group, in order to obtain greater control about the projects formulated in the different organizations that make it up, establishing a clear hierarchization and prioritization of the projects. To achieve the specific objectives set forth, the methodology of explanatory qualitative research was used, which can be defined as the research that produces descriptive data by being inductive, understanding the context and allowing going from the general to the specific and thus recognize, evaluate and determine the needs of implementation of the project portfolio management model in the Empresarial del Llano Group. As a complement to the above, the particular and specific method was used, through observations supported by interviews, which were used as primary sources to know the activities developed around the management of project portfolios in the organization. As secondary sources we used the PMI portfolio standard (3rd edition), the strategic planning of the organization, as well as guidelines, methodologies and related information and published with the topic of project portfolio management in different organizations. The techniques used for the investigation were expert judgment, information analysis, literature review, internet search and brainstorming; Field investigations were carried out supported by the survey and the interview, which were applied to different stakeholders of the Project Portfolio Management and the strategic planning of the companies analyzed. Although there were other standards for the management of the project portfolio, among them the "The Standard of Portfolio Management" and the "International Project Management Association", which is one of the leading associations in the certification of competencies in project management, programs and portfolios, in Spain; The justification for the selection of the PMI standard is due to the fact that there is more information available to organizations, allowing in this way to have established references that guarantee the proper development of the proposed work supported with a series of processes, tools and techniques to manage a portfolio of projects that provides the expected value for the organization studied. The proposed degree work sought to design a corporate portfolio management model in the Empresarial del Llano Group, so as to maximize the value of the projects for the organization, which are aligned with the strategic objectives and the allocation of resources It will be done in a balanced way. On the other hand, it is advisable to indicate that there is support from top management to carry out this degree work, since it is essential for the resources that are needed and that involves a good management of the projects. with people willing to change, you agree that the implementation and good management of this proposal is necessary to achieve success in the change in the organizational culture, supported by a good communication system with all the parties involved.